1/6 type diffraction patterns and double P-E hysteresis loops in Bi(Mg2/3Nb1/3)O3 modified NaNbO3 ceramics. (27th May 2020) - Li, Wei; Xia, Xiang; Zeng, Jiangtao; Zheng, Liaoying; Man, Zhenyong; Li, Guorong
Abstract: To promote the development of NaNbO3 -based antiferroelectrics, it is necessary to stabilize the antiferroelectric phase over ferroelectric phase through compositional design strategy. In this work, Bi(Mg2/3 Nb1/3 )O3 was doped into NaNbO3 for decreasing the Goldschmidt tolerance factor, and double P-E hysteresis loop was observed. Raman spectra showed the enhanced antiferroelectricity in Bi(Mg2/3 Nb1/3 )O3 doped samples, and 1/6(100) rather than the usually reported 1/4(100) diffraction spots were observed from selected area electron diffraction patterns. This work is helpful in promoting the research of NaNbO3 -based antiferroelectric systems.